Sistem Perparkiran Mobil Vertikal di Rumah - Tjiharjadi, Semuil; Hermawan, Ferdian (Zenit, 2013)
Nowaday, people are getting busier every day. Most of them have to live far away from their school or business activity. Because of that they  need more cars to support their transportation. One for the father, one for the mother and one for their children. Meanwhile, the price of houses and land is getting higher. This situation results in parking problem. The main issue of this paper is how to park cars  easily and quickly. This question triggers an idea to create a system that can facilitate vertical car parking at home. This system is controlled by HMI (Human Machine Interface) which can support real-time parking system. The system can store 3 cars in a garage.  This process is controlled by a microcontroller. Users can choose a selection of  slot buttons. This process can work well  if all conditions are met. Based on the experiments of the system, the average time of  storing process is 11 seconds and the average time of taking the car from storage is 9 seconds. The average time of several experiments is 10 seconds.  Keywords: Microcontrollers, Vertical Parking System